Educational Programming to Prevent Violence in Schools in the United States: An Analysis of School Health Profiles - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott; Benes, Sarah (The Journal of Pediatrics, 2025)
This repeated, cross-sectional study examined trends in the availability of school-based programming to prevent violence in middle and high schools across the United States from 2008 to 2020. Overall, violence prevention programming increased in respondent schools throughout the study period. However, important gaps remain, with lingering state-level disparities.
Keywords: Human factors and ergonomics; Injury prevention; Occupational safety and health; Poison control; Respondent; Suicide prevention; adolescent health; dept.hms; health education; school violence prevention; teacher training; youth violence prevention